PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA SMP PADA MATERI STATISTIKA - Zulfa Dasti Fitriani; Masta Hutajulu; Eva Dwi Minarti (IKIP Siliwangi, 2023)
Covid-19 is a rapidly growing outbreak around the world, one of the obvious impacts is the education sector. Inadequate education affects the learning outcomes of learners. One of the factors that affect student learning outcomes is the presence of motivation that comes from the student itself. Without the willingness to learn, it can be difficult for students to know what to learn and why they need to learn it. The research used is correlational and ex-post facto research using quantitative approaches that aim to find out whether students' learning outcomes in statistical material have an effect on learning motivation. The subjects used in the study were class IX students consisting of 6 students including 3 women and 3 men. Research instruments conducted using student motivation scale questionnaires and written tests of statistical material. The data analysis technique used in this study is a simple linear regression analysis using an average percentage of motivational indicators and spsss statistic 25 software. The results of the study proved that there was an influence of 62.2% between learning motivation and student learning outcomes.